2019
DOI: 10.25208/0042-4609-2019-95-2-15-28
|View full text |Cite
|
Sign up to set email alerts
|

Netakimab — new IL-17а inhibitor: 12-week results of phase III clinical study BCD-085-7/PLANETA in patients with moderate-tosevere plaque psoriasis

Abstract: Netakimab, the original monoclonal antibody against IL-17A, is an innovative drug for the treatment of moderate-to-severe plaque psoriasis in patients who have indications for systemic therapy or phototherapy. Netakimab was approved in Russian Federation, registration certificate number ЛП-005439 from 04.04.2019. This article outlines the first 12-week results of a phase III clinical trial in patients with psoriasis.Materials and methods. The BCD-085-7 study (PLANETA) is a comparative, randomized, double-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
2
2
0
3
Order By: Relevance
“…Preliminary results of BCD-085-7/PLANETA study (NCT03390101), a comparative, randomized, double-blind, placebo-controlled phase III clinical study, showed that at week 12 PASI75 was achieved by 83.3% and 77.7% of the patients treated with netakimab 120 mg every four and every two weeks, respectively, compared to 0% in placebo arm. 15–17 The drug showed a favorable safety profile consistent with those expected for the class of IL-17 inhibitors, and low immunogenicity. 15 Finally, the results of the 24-week period phase III clinical trial (PATERA study) investigating the efficacy and safety of netakimab compared to placebo in patients with active psoriatic arthritis showed that netakimab 120 mg is significantly superior to placebo in patients with active psoriatic arthritis.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Preliminary results of BCD-085-7/PLANETA study (NCT03390101), a comparative, randomized, double-blind, placebo-controlled phase III clinical study, showed that at week 12 PASI75 was achieved by 83.3% and 77.7% of the patients treated with netakimab 120 mg every four and every two weeks, respectively, compared to 0% in placebo arm. 15–17 The drug showed a favorable safety profile consistent with those expected for the class of IL-17 inhibitors, and low immunogenicity. 15 Finally, the results of the 24-week period phase III clinical trial (PATERA study) investigating the efficacy and safety of netakimab compared to placebo in patients with active psoriatic arthritis showed that netakimab 120 mg is significantly superior to placebo in patients with active psoriatic arthritis.…”
Section: Resultssupporting
confidence: 57%
“… 15–17 The drug showed a favorable safety profile consistent with those expected for the class of IL-17 inhibitors, and low immunogenicity. 15 Finally, the results of the 24-week period phase III clinical trial (PATERA study) investigating the efficacy and safety of netakimab compared to placebo in patients with active psoriatic arthritis showed that netakimab 120 mg is significantly superior to placebo in patients with active psoriatic arthritis. In this study PASI75, PASI90 and PASI100 were reported as secondary endpoints ( Table 1 ).…”
Section: Resultssupporting
confidence: 57%
“…Профиль безопасности 54 недель применения НТК у пациентов с ПсА соответствовал профилям безопасности НТК при применении у пациентов с псориазом и анкилозирующим спондилитом [8,9]. В большинстве случаев НЯ были не связаны с активной терапией, по мнению исследователей, и имели легкую и среднюю степени тяжести.…”
Section: Discussionunclassified
“…Нетакимаб (НТК) -оригинальное рекомбинантное гуманизированное моноклональное IgG1 антитело против ИЛ-17А. В исследованиях III фазы у пациентов с бляшечным псориазом (BCD-085-7/PLANETA, NCT03390101) и анкилозирующим спондилитом (BCD-085-5/ASTERA, NCT03447704) установлено превосходство НТК над плацебо, а также долговременная эффективность и безопасность препарата [8,9]. BCD-085-8/ PATERA -клиническое исследование (КИ) III фазы, направленное на определение эффективности и безопасности применения НТК у пациентов с активным ПсА (NCT03598751).…”
Section: Efficacy Of Netakimab In Key Psoriatic Arthritis Domains: 54unclassified
“…Так, к 12-й нед. терапии нетакимабом в зарегистрированном режиме дозирования среднее снижение проявлений ониходистрофии составило 52% относительно исходных значений [55].…”
Section: эффективность блокаторов ил-17 при псориазе с поражением ногunclassified